Lobachevskii Journal of Mathematics
Vol. 13, 2003, 39 – 43
©Kulwinder Kaur
Kulwinder Kaur
TAUBERIAN CONDITIONS FOR
L1-CONVERGENCE
OF MODIFIED COMPLEX TRIGONOMETRIC SUMS
(submitted by F. G. Avkhadiev)
________________
2000 Mathematical Subject Classification. 42A20, 42A32.
|
ABSTRACT. An L1–convergence
property of the complex form gn(c,t) = Sn(c,t) −cnEn(t) + c−nE−n(t)
of the modified sums introduced by Garrett and Stanojević
[3] is established and a necessary and sufficient condition for
L1-convergence
of Fourier series is obtained.
1. Introduction.
Let Sn(f,t) and
σn (f,t) denotes the
nth partial sum and
nth Cesàro means of
the Fourier series ∑
n<∞cneιnt,t ∈ T = R
2πZ
respectively. Define △f̂(n)as
follows: for n > 0,
△f̂(n) = f̂(n) −f̂(n + 1) and
△f̂(−n) = f̂(−n) −f̂(−n − 1).
If the trigonometric series is the Fourier of some
f ∈ L1(T), we shall
write cn = f̂(n) for
all n, and Sn(c,t) = Sn(f,t) = Sn(f).
Also gn(c,t) = gn(f,t) = gn(f).
Many authors have defined
L1 -convergence
classes in terms of the conditions on the sequences of the
Fourier coefficients as there exists an integrable function on
T
whose Fourier series does not converge to itself in
L1 -norm. An
L1 -convergence class is a class
of Fourier coefficients {f̂(n)}for
which
Sn(f,t) − f(t) = o(1)(n →∞),
| (1.1) |
if and only if f̂(n) log n = o(1)
(n →∞).
The following is the well-known
L1 −convergence
class for Fourier series:
lim λ↓1 lim n →∞___ ∑
k=nλn kp−1 Δf̂(k) p = 0.(1 < p ≤ 2)
| (1.2) |
The above condition (1.2) is a Tauberian condition of Hardy-Karamata kind and
is weaker than those considered by Fomin [2], Kolmogorov [4], Littlewood [5] and
Telyakovskii [7]. Stanojevic [6] proved the following Tauberian Theorem for
L1 −convergence
of Fourier series of complex valued Lebesgue integrable functions on
T = R
2πZ.
Theorem[3]. Let f ∼∑
n<∞cneιnt
be a Fourier series of f ∈ L1(T),
whose coefficients satisfy
1
n ∑
k=1n f̂(k) −f̂(−k) log k = o(1)(n →∞),
| (1.3) |
lim λ↓1 lim n →∞___ ∑
k=nλn △f̂(k) −f̂(−k) log k = 0.
| (1.4) |
If for some 1 < p ≤ 2,
lim λ↓1 lim n →∞___ ∑
k=nλnkp−1 Δf̂(k) p = 0,
| (1.5) |
then Sn(f) − f = o(1)(n →∞),
if and only if
f̂(n)En(t) + f̂(−n)E−n(t) = o(1)(n →∞)
| (1.6) |
where En(t) =
∑
k=0neιnt.
Sequences satisfying conditions (1.3) and (1.4) are called asymptotically even.
In the case of even or odd coefficients, condition (1.6) is equivalent with
f ̂ (n) log n = o(1)
(n →∞).
The object of this paper is to study the
L1 -convergence
of the complex form
gn(c,t) = Sn(c,t) −f̂(n)En(t) + f̂(−n)E−n(t)
| (1.7) |
of the modified sums introduced by Garrett and Stanojević [3] and to obtain the
above mentioned theorem of
Stanojević [6] without the notion of asymptotic evenness.
2. Lemma.
We shall use the following Lemma for the proof of our result:
Lemma[1]. For each non-negative integer
n, there
holds
f̂(n)En(t) + f̂(−n)E−n(t) = o(1)(n →∞)
if and only if
f̂(n) log n = o(1)(n →∞),
where {f̂(n)} is
a complex null sequence.
3. Main Result
The main result of this paper is the following theorem:
Theorem. Let f ∼∑
n<∞cneιnt be
a Fourier series of f̂ ∈ L1(T).
If for some 1 < p ≤ 2,
lim λ↓1 lim n →∞___ ∑
k=nλn kp−1 Δf̂(k) p = 0,
| (3.1) |
then
(i) gn(f,t) − f(t) = o(1)(n →∞).
(ii) Sn(f,t) − f(t) = o(1)(n →∞), if
and only if
f̂(n) log n = o(1)(n →∞).
Here and in the sequel, . means the
greatest integral part and .denotes
L1 (T)-norm:
f = 1
π ∫
0π f(t) dt
We draw three corollaries of the above theorem:
Corollary 1. If f ∈ L1(T)
and for some 1 < p ≤ 2,
the limit
lim n→∞1
n ∑
k=1n kp Δf̂(k) p
| (3.2) |
exists and is finite, then we have both part
(i) and
(ii) of the
theorem.
Corollary 2. If f ∈ L1(T)
and for some 1 < p ≤ 2,
∑
k=1∞kp−1 Δf̂(k) p < ∞,
| (3.3) |
then we have both part (i)
and (ii)
of the theorem.
It is well known that (3.3)
implies the existence of (3.2),
and the latter implies (3.1).
Corollary 3. If f ∈ L1(T)
and for some 1 < p ≤ 2,
lim λ↓1 lim n →∞___ ∑
k=nλn λn − k
λn − np kp−1 Δf̂(k) p = 0,
| (3.4) |
then
lim λ↓1 lim n →∞___ gn(f,t) − f(t) = o(1)(n →∞),
and Sn(f,t) − f(t) = o(1)(n →∞),
if and only if
f̂(n) log n = o(1)(n →∞).
Also corollary 1 extends for coefficient sequences satisfying
(3.4) instead
of (3.1).
Proof of Theorem.
Let λ > 1
and n > 1,
then we have
V nλ(f,t) − f(t) = λn+1
λn−n σλn(f,t) − f(t) − n+1
λn−n σn(f,t) − f(t)
where V nλ(f,t) = 1
λn−n ∑
k=n+1λnS
k(f,t)
is the generalized de Ia Vallée-Poussin means.
And σn(f,t) = 1
n+1 ∑
k=0nS
k(f,t)
Since σn(f,t) − f(t) = o(1)(n →∞),
then it follows that
V nλ(f,t) − f(t) = o(1)(n →∞).
Consequently it is sufficient to prove that
lim λ↓1 lim n →∞___ V nλ(f,t) − g
n(f,t) = 0.
| (3.5) |
Elementary calculation gives
V nλ(f,t) − S
n(f,t) = ∑
k=n+1λn λn −k + 1
λn − n f̂(k)eιkt
By (1.7), we have
V nλ(f,t)−g
n(f,t) = ∑
k=n+1λn λn −k + 1
λn − n f̂(k)eιkt+f̂(n)E
n(t)+f̂(−n)E−n(t)
| (3.6) |
By using summation by parts, we get
∑
k=n+1λnλn−k+1
λn−n f̂(k)eιkt
=∑
k=n+1λn−1△λn−k+1
λn−n f̂(k) Ek(t) + 1
λn−nf̂(λn)Eλn(t) −f̂(n + 1)En(t)
=∑
k=n+1λn−1 λn−k
λn−n△f̂(k)Ek(t) + 1
λn−nf̂(k)Ek(t)
+ 1
λn−nf̂(λn)Eλn(t) −f̂(n + 1)En(t)
=∑
k=nλnλn−k
λn−n△f̂(k)Ek(t) + 1
λn−n ∑
k=n+1λnf̂(k)E
k(t) −f̂(n)En(t)
Similarly
∑
k=n+1λnλn−k+1
λn−n f̂(−k)e−ιkt
=∑
k=nλnλn−k
λn−n△f̂(−k)E−k(t) + 1
λn−n ∑
k=n+1λnf̂(−k)E
−k(t) −f̂(−n)E−n(t)
Therefore
V nλ(f,t) − g
n(f,t)
=∑
k=nλnλn−k
λn−n △f̂(k)Ek(t) + 1
λn−n ∑
k=n+1λnf̂(k)E
k(t)
Note that
V nλ(f,t) − g
n(f,t) = 1
π ∫
0π
n + ∫
π
n π V
nλ(f,t) − g
n(f,t) dt
= I1 + I2
For the first integral, we have the following estimate from
(3.5)
I1 ≤ 1
n ∑
k=n+1λnλn−k+1
λn−n f̂(k) ≤ 1
n ∑
k=n+1λn f̂(k) = o(1)(n →∞),
since {f̂(n)} = o(1)(n →∞).
Therefore (3.2)
holds if and only if
limλ↓1lim n →∞___ ∫
π
n π V
nλ(f,t) − g
n(f,t) dt = 0.
To estimate I2
V nλ(f,t) − g
n(f,t) = ∑
k=nλnλn−k
λn−n △f̂(k)Ek(t) + 1
λn−n ∑
k=n+1λnf̂(k)E
k(t)
= In1 + In2
After applying Ho¨lder-inequality
and then the Hausdorff-Young inequality to
In2 , we
have
In2 ≤ Cp n
λn−n 1
q 1
λn−n ∑
k=n+1λn f̂(k) p 1
p
Similarly
In1 ≤ Bp ∑
k=nλn kp−1 △f̂(k) p 1
p
where Cp and
Bp are absolute constants
depending on p,
and 1
p + 1
q = 1.
Since{f̂(n)} is a null
sequence and λ > 1,
we have
limλ↓1lim n →∞___In2 = 0.
Hence
gn(f,t) − f(t) ≤gn(f,t) − V nλ(f,t) + V
nλ(f,t) − f(t)
≤ λn + 1
λn − n σλn(f,t) − f(t + n + 1
λn − n σn(f,t) − f(t
+ Bp ∑
k=nλn kp−1 △f̂(k) p 1
p
| (3.7) |
Also as f ∈ L1(T), it
follows that σn(f,t) − f(t) = o(1)(n →∞).
Taking lim
sup of
both sides of (3.6), we have
limn →∞___ gn(f,t) − f(t) ≤ Bp lim n →∞___ ∑
k=nλn kp−1 △f̂(k) p 1
p .
By taking lim
as λ ↓ 1
and by condition (3.1), we obtain
lim λ↓1 lim n →∞___ gn(f,t) − f(t) = 0.
(ii)
Sn (f,t) − f(t) ≤Sn(f,t) − gn(f,t) + gn(f,t) − f(t)
= gn(f,t) − f(t) + f̂(n)En(t) + f̂(−n)E−n(t) ,
f̂(n)En(t) + f̂(−n)E−n(t) = gn(f,t) − Sn(f,t)
≤gn(f,t) − f(t) + Sn(f,t) − f(t)
Since gn(f,t) − f(t) = o(1),
(n →∞) by
(i) and
by Lemma,
f̂(n)En(t) + f̂(−n)E−n(t) = o(1)(n →∞),
if and only if f̂(n) log n = o(1)
(n →∞).
Therefore Sn(f,t) − f(t) = o(1)(n →∞),
if and only if f̂(n) log n = o(1)
(n →∞).
This proves part (ii)
References
- W.O. Bray and Č.V. Stanojević, Tauberian L1-convergence
class of Fourier series, Trans. Amer. Math.Soc. 275(1983), 59-69
- G.A. Fomin, A class of trigonometric series, Mat. Zametki 23 (1978),
213-222.
- J.W. Garrett and Č.V. Stanojević, On L1-
convergence of certain cosine sums, Proc. Amer. Math. Soc. 54(1976),
101-105.
- A.N. Kolmogorov, Sur I’, Ordre des coefficients de Ia serie de
Fourier-Lebesgue, Bull. Acad. Polon. Ser. Sci. Math. Astronom Phys.
(1923), 83-86.
- J.E. Littlewood, The convergence of Abel’s Theorem on power series,
Pro. London. Math. Soc., 9(1911), 434-448.
- Č.V. Stanojević, Tauberian conditions L1-convergence
of Fourier series, Trans. Amer. Math. Soc.271(1982), 237-244.
- S.A. Telyakosvskii, On conditions of integrability of multiple
trigonometric series, Trudy Mat. Inst.Steklov. 164(1983), 180-188
(Russian).
- A. Zygmund. Trigonometric Series, Cambridge University Press, 1959.
GOVT. POLYTECHNIC INSTITUTE, BATHINDA.15100 PUNJAB. INDIA
E-mail address: mathkk@hotmail.com